ICMR Consensus Guidelines on ‘Do Not Attempt Resuscitation’ - Roli Mathur (2020)
Cardiopulmonary resuscitation (CPR) is widely practised by healthcare professionals to revive heart beat and breathing in a patient suffering from cardiac/ respiratory arrest. It is increasingly being recognized that in some patients with specific medical conditions, CPR does not alter the overall outcome of illness, and is likely to increase suffering and further deteriorate the quality of life. Do Not Attempt Resuscitation (DNAR) as an option has been practised in many countries for such cases to avoid futile CPR and maintain dignity of the patient. The decision of DNAR should be taken by the treating physician who is well versed with the patient's medical condition, with information to the patient or her/his surrogate. While ordering DNAR on the patient's medical case record, every effort should be made to treat the underlying disease and continue optimal medical care with compassion. This policy document describes the principles for DNAR, offers an algorithm and format for its implementation, and guidance on frequently asked questions.